Governance ideas in Kong-Zi Jiayu and their contemporary values - Li, Hua (2023)
Kong-Zi Jia Yu is a book that recorded many Confucius and his disciples’ conversations and thoughts, making it an indispensable source to explore traditional Chinese culture and ideas. In particular, the governance ideas presented in the book are still highly relevant today. People-oriented thoughts were the core of governance wisdom, paradigmatic kingcraft and virtuous courtiers were a sensible part of governance, and the penological ideas further ensured the robust operations of it. In the new era, new ideas like “putting the people as the top priority”, Xi Jinping’s thoughts on building cadre teams and governing China by the rule of law have successively proposed as creative converts and innovative development of Chinese culture that has been carried forward over thousands of years. Inheriting and promoting these cultural "genes", refining their ideological essence, are of great reference value for cultivating the current political landscape, enriching the connotation of the construction of the cadre team in the new era, adhering to the rule of law and providing ideas for the formulation of current rural governance policies.